Gender-affirming multidisciplinary care for transgender and non-binary children and adolescents. Issue 1 (2nd January 2023) - Warwick, Rebecca M.; Shumer, Daniel E.
ABSTRACT: Modern transgender and non-binary (TGNB) pediatric health care originated in the 1990s. This patient population is adversely affected by minority stress, victimization, mental health disparities, and barriers to health care With improving social and cultural support for TGNB identities and favorable evidence for affirming social and medical interventions, the need for pediatric gender services clinics has grown. Gender-affirming care requires collaboration between social and medical entities, including school personnel, community services, medical providers, and mental health professionals, which is best served within a multidisciplinary treatment model of care. This article provides an overview of the components within multidisciplinary pediatric gender clinics.